2017
DOI: 10.2147/copd.s124051
|View full text |Cite
|
Sign up to set email alerts
|

Global scientific collaboration in COPD research

Abstract: PurposeThis study aimed to investigate the multiple collaboration types, quantitatively evaluate the publication trends and review the performance of institutions or countries (regions) across the world in COPD research.Materials and methodsScientometric methods and social network analysis were used to survey the development of publication trends and understand current collaboration in the field of COPD research based on the Web of Science publications during the past 18 years.ResultsThe number of publications… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 20 publications
1
12
1
1
Order By: Relevance
“…Visualization analysis of cooperation among countries suggests that China, the USA and Australia are the most productive countries and are also the hotspots for the study of adolescent myopia prevention and control. Compared with other studies indicating that collaborative countries are often geographically interrelated (32), our results present conflicting outcomes considering the distribution of seven major clusters. In the co-authorship network of countries, the developed countries occupy the vast majority.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Visualization analysis of cooperation among countries suggests that China, the USA and Australia are the most productive countries and are also the hotspots for the study of adolescent myopia prevention and control. Compared with other studies indicating that collaborative countries are often geographically interrelated (32), our results present conflicting outcomes considering the distribution of seven major clusters. In the co-authorship network of countries, the developed countries occupy the vast majority.…”
Section: Discussioncontrasting
confidence: 99%
“…We found that, in the past 20 years, the total number of papers in the field of prevention and control of myopia in adolescents, as well as the total number of co-authored articles, increased especially since 2011. Previous studies in other research fields showed a similar trend (15, 32).…”
Section: Discussionsupporting
confidence: 81%
“…Overall, 15,999 articles in research were published by 8425 institutions. Fifteen institutes were selected because of their critical role for scientific knowledge dissemination [19,20]. The list of top 15 institutions is presented in Table 2, which published about 24.81% of all the articles.…”
Section: Characteristics Of the Institutions Contributionmentioning
confidence: 99%
“…Successful team science demands effective collaboration to gain needed resources and expertise. Indeed, research impact upon a given discipline appears increasingly associated with domestic and international scientific collaboration [ 4 , 5 ]. The ability to establish productive research collaborations is one of the measures proposed to evaluate RCMI Center success [ 6 ].…”
Section: Introductionmentioning
confidence: 99%